Beyond the BRAFV600E hotspot: biology and clinical implications of rare BRAF gene mutations in melanoma patients. (1st October 2017) - Richtig, G.; Hoeller, C.; Kashofer, K.; Aigelsreiter, A.; Heinemann, A.; Kwong, L.N.; Pichler, M.; Richtig, E.
Summary: BRAF gene mutations can be found in approximately 50% of melanomas, but the most common BRAF mutation leads to substitution at residue 600 of the protein, from valine to glutamic acid. BRAF V 600E occurs in up to 95% of all melanoma cases and can be successfully blocked by using a combination of BRAF‐ and MEK inhibitors. The wider availability of next‐generation sequencing is revealing more non‐V600 BRAF mutations, and the clinical implications of these mutations are widely unknown. In this review, we will discuss the biology of the MAPK pathway and the different types of BRAF mutations as well as their effect on MEK activation. Current literature will be reviewed including in vitro data, case reports and case series.